Eco-Friendly Approach to Palm Oil Biodiesel Production: Torrefied Palm Frond Carbon as a Source for CaO/C/NaOH Catalysts - Helwani, Zuchra; Amraini, Said Zul; Asmura, Jecky; Othman, Mohd. Roslee; Peliciamanuela, Samantha; Anggriani, Rara Dewi (Heca Sentra Analitika, 2024)
Biomass-based sources for energy generation have attracted much attention recently due to its environmental benefits. These days, using edible oils and alkali catalysts, such as CaO, is standard practice for the transesterification step of the biodiesel synthesis process. Glycerine and methanol will form hydrogen bonds with the oxygen ions on the CaO surface, increasing the viscosity of the glycerine and causing CaO to suspend. Even though CaO was utilized directly as a catalyst in the transesterification process, extracting the CaO and glycerine from the final product will be challenging. To solve this issue, any extra metal oxides or catalyst supports ought to be impregnated into the CaO. This work has investigated the possible use of eggshells and palm fronds in developing bifunctional catalysts for biodiesel production. A series makes the processes' catalyst, including impregnation, calcination, and torrefaction. To assess the catalyst's performance, the esterification and transesterification of palm oil with a 2.9% free fatty acid content were investigated at a methanol/oil ratio of 6:1, catalyst concentration of 1-3% by weight, reaction temperature of 70 °C, and duration of 3 hours. The catalyst was found to have a specific surface area of 8.266 m2/g. There was an 89.4% yield of biodiesel produced. A viable, economical, and ecologically friendly method of producing biodiesel is to use eggshells and palm fronds in catalyst synthesis.